2014
DOI: 10.1179/2045772314y.0000000215
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of some non-conventional herbal medications (sulforaphane, tanshinone IIA, and tetramethylpyrazine) in inducing neuroprotection in comparison with interleukin-10 after spinal cord injury: A meta-analysis

Abstract: IL-10 has a strong effect in the induction of neuroprotection and neurorecovery after SCI by multiple pathways. Tetramethylpyrazine has an acceptable influence in reducing inflammation through the up-regulation of IL-10. Outcomes of sulforaphane and tanshinone IIA administration are acceptable but still weaker than IL-10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 66 publications
2
14
0
Order By: Relevance
“…We also confirmed that tan IIA prevented streptozotocininduced memory deficits in mice [20]. Recently, our experimental data revealed that tan IIA inhibited endoplasmic reticulum stress-induced apoptosis in APPswe/ PS1dE9 (referred to as APP/PS1) transgenic mice and SH-SY5Y cells [24,25], although increasing evidence showed that tan IIA exhibits anti-inflammatory activity both in vivo and in vitro [21,[26][27][28]. However, the effects of tan IIA on RAGE-mediated neuroinflammation and its underlying molecular mechanisms in AD are not reported.…”
Section: Introductionsupporting
confidence: 78%
“…We also confirmed that tan IIA prevented streptozotocininduced memory deficits in mice [20]. Recently, our experimental data revealed that tan IIA inhibited endoplasmic reticulum stress-induced apoptosis in APPswe/ PS1dE9 (referred to as APP/PS1) transgenic mice and SH-SY5Y cells [24,25], although increasing evidence showed that tan IIA exhibits anti-inflammatory activity both in vivo and in vitro [21,[26][27][28]. However, the effects of tan IIA on RAGE-mediated neuroinflammation and its underlying molecular mechanisms in AD are not reported.…”
Section: Introductionsupporting
confidence: 78%
“…Mounting evidence has shown that besides of the benefit of endogenous IL-10, exogenous IL-10 also had obvious neuroprotection and neuro-recovery properties in animal models; even more efficient than some anti-inflammatory and anti-oxidative agents [53]. Considering these data together with the findings from this study, IL-10 may be a potentially useful drug for the treatment of diabetic neuropathy.…”
Section: Discussionsupporting
confidence: 66%
“…The results showcased the protective ability of PA in PC12 cells against H 2 O 2 -evoked impairment, which was presented as accelerating cell viability, repressing TCMs have been shown the effective functions in remedying SCI, especially S. miltiorrhiza [15,16]. The existing evidences attest that S. miltiorrhiza emerges a beneficial role in impeding secondary damage after acute SCI, which also can fight cell apoptosis and accelerate nerve repair [17,18]. A rat SCI model experiment disclosed that the extractions from S. miltiorrhiza could effectively relieve SCI [19].…”
Section: Discussionmentioning
confidence: 92%